The Descriptive Analysis of the Implementation of the Adiwiyata Program at SDN Brenggong: Analisis Deskriptif Pelaksanaan Program Adiwiyata di SDN Brenggong - Latoifit Toharoh (International Journal of Technology Vocational Education and Training, 2021)
This study aims to describe the implementation of the Adiwiyata program at SDN Brenggong which includes 4 components of the Adiwiyata program and the obstacles in the implementation of the Adiwiyata program at SDN Brenggong. This research is a qualitative research, with a descriptive approach. Data collection instruments, namely the research themselves with tools in the form of observation guidelines, interviews and documentation that have been validated by one validator. Data validity test uses Miles and Huberman models using reference materials, namely the existence of support to prove the data has been found. The result show that the implementation of environmentally sound policies has been carried out by changing the vision and mission that supports environmental management and the allocation of funds for the Adiwiyata program, the curriculum applied is the 2013 curriculum integrated with an environmentally sound curriculum that is inserted in every lesson on the theme and includes self-development activities, namely environmental education is included in extracurricular activities, participatory-based environmental activities are carried out intensively both inside and outside schools by involving other agencies and the management of environmentally friendly supporting facilities is carried out intensively by school residents (2) The obstacles in implementing the Adiwiyata program are the condition of students who are not fully aware of environmental sustainability, the costs to support Adiwiyata facilities and programs as well as the time and personnel of school residents, especially teachers and employees, because they have to fully manage facilities and facilities in schools during the Covid 19 pandemic.